Caracterización morfo-agronómica de 51 selecciones élites de plátano cv. Barraganete (Musa AAB Simmonds) en el valle del río Carrizal - Cedeño Vera, Juliana Lisbeth (2023)
The objective of the research was to characterize morphologically and agronomically 51 elite selections of plantain cv. Barraganete (Musa AAB Simmonds). The work was carried out during the year 2022 in the polytechnic field at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. The treatments were made up of 51 elite selections of plantain cv. Barraganete with four replicates per treatment. The morpho-agronomic variables evaluated were plant height, pseudostem perimeter, number of leaves, leaf area, gross and net weight of bunch, number of hands and fruits per bunch, length, diameter and fruit weight. The data were analyzed through analysis of variance and separation of means with Tukey's test (p<0.05). The results reported significant statistical differences (p<0.05) for the variables pseudostem perimeter, leaf area, number of fruits, number of hands, gross weight and net weight of the cluster, where 20 elite clones exceeded the average of the 51 elites selections evaluated, of which clones 130356-11, 130302-9, 130401-10, 130452-11 and 130356-10 reached the highest averages in productive potential, so they could be selected for a next phase of evaluation in several locations of the area of influence on the Carrizal River valley.